Enhancing biogas and methane production from leaf litter of neem by co-digestion with vegetable waste: Focus on the effect of tannin. (April 2021) - Muhammad, M.B.; Chandra, R.
Abstract: Leaf litter of neem (LLN) represents a critical part of organic waste trashing our immediate environment. The current solution for its management is unsatisfactory. This paper presents a new approach to treat the waste. It examines the effect of LLN on biogas composition produced from vegetable waste (VW) and cattle dung (CD). Anaerobic co-digestion of LLN with VW (R1), mono-digestion of VW (R2), mono-digestion of LLN (R3), and co-digestion of VW with CD (R4) were conducted under mesophilic conditions. R1 and R4 produced higher biogas and methane than R2. The introduction of LLN to VW improved biogas and methane yields by 87.27 and 91.47% and reduced H2 S by 146.73% compared to R2. The maximum methane content of R1 suffices for electricity and heat generation. It can help in comprehending another way of managing LLN and optimization of process conditions. Highlights: Effect of leaf litter of neem (LLN) on the methane production was investigated. Co-digestion of vegetable wastes with LLN improved methane yield. But significantly reduced formation of hydrogen sulfide. Saponin content of LLN adversely affects biogas and methane production.